FACTORS AFFECTING FIRM VALUE WITH DIVIDEND POLICY AS MODERATION - Winnie, Xaviera; Sufiyati, Sufiyati (Graduate Program of Universitas Tarumanagara, 2024)
The purpose of this study was to analyze how profitability, liquidity, company growth, company age and leverage affect firm value with dividend policy as a moderating variable in companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2022. The total research sample was taken from companies with the consumer non-cyclicals sector selected by purposive sampling method. The data in this study are secondary data in the form of financial reports taken from the official IDX website. The total company data used in accordance with the research criteria were 81 research samples and after outliers became 65 research samples. The data of this study were analysed using multiple linear regression analysis techniques processed with SPSS (Statistical Product and Service Solutions) software version 26. The results of this study indicate that profitability and dividend policy have a significant positive effect on firm value. Liquidity, company growth and company age have no significant effect on firm value. Dividend policy does not moderate the effect of profitability, liquidity and company growth on firm value. This study provides important knowledge to company management to pay attention to factors that affect firm value.